Micro Mineral Concentration in Soil, Plant and Dairy Cattle in Andaman Group of Islands - Hegde, M. Sujata; ., Jaisunder; Kumaresan, A.; Datt, Chander; Singh, Pawan; Singh, Avtar (Indian Journal of Animal Nutrition, 2018)
The present work was undertaken with the aim to estimate minerals status in soil, composite plant samples and dairy cattle in six blocks viz., Prothrapur, Ferrargunj, Little Andaman, Diglipur, Rangat and Mayabunder of Andaman group of islands. A total of 102 samples each of soil, composite plant and cattle blood serum were taken randomly from each block. All the samples were analysed for estimation of micro minerals (Zn, Fe, Mn, Cu and Co). The results revealed that the overall mean concentration of Zn (1.25±0.27 ppm), Fe (76.02±10.54 ppm), Mn (37.66±5.04 ppm) and Cu (1.61±0.32 ppm) in soil was higher than the critical level and differed significantly (P<0.05) among the blocks. In feed materials, the level of Fe, Mn Cu and Co was 220.09±38.54, 66.41±8.02, 10.54±2.15 and 0.17±0.01 ppm, respectively and was found to be higher than the critical levels. In cattle blood serum, the overall mean of Zn, Cu, Co was found to be 0.95±0.11, 0.56±0.11 and 0.17±0.01ppm, respectively. The concentration of these minerals was below the critical level and a significant (P<0.01 and P<0.05) variation was found among blocks with regard to Zn and Cu concentration. Overall incidence (%) of deficiency in cattle blood serum was found to be 60.78, 45.1 and 15.69% for Zn, Cu and Co, respectively. The incidence (%) of deficiency was more than 50% for Zn in Prothrapur and Little Andaman block and was above 80% in Ferrargunj block. The correlation between composite plant and cattle was positive (P<0.01) for Fe (r=0.411) and (P<0.05) for Cu (r=0.210) and non-significant for Zn, Mn and Co. Therefore, it could be concluded that the soils were deficient in Zn, plants in Zn, Cu and Co while cattle were deficient in all the minerals, hence, a suitable area specific mineral mixture need to be developed to improve the production and reproduction performances in dairy cattle in the area under study.